MASTERY OF GENERAL CHEMISTRY IN STUDENTS ON THE BASIS OF INFORMATION MODELS IS THE PROCESS OF FORMATION OF SKILLS (American Journal of Pedagogical and Educational Research, 2023)
In this article, there is an opinion that students should consider chemical reactions and processes that are generalized from general chemistry as their own characteristics. That is, it is shown that the generalization and mastery of each formed skill is based on a certain rule.